Sistem Pendukung Keputusan Menentukan Mutasi Karyawan Menggunakan Metode ORESTE - Diah Sawitri; Aninda Muliani Harahap (KLIK: Kajian Ilmiah Informatika dan Komputer, 2024)
Employee transfer is one aspect that influences employee performance in a company. PT PLN (Persero) ULP Labuhan is one of the agencies or companies that implement transfers with the aim of improving employee performance. With the increasingly advanced development of technology, every company is competing to keep up with the times. Employee transfers at PT PLN (Persero) ULP Labuhan are still carried out manually and decisions are made only based on individual or group opinions. Therefore, determining which employees will be transferred takes a long time and produces less than optimal results. This study aims to help PT PLN (Persero) ULP Labuhan identify employee transfers that will provide maximum results. In this study, the waterfall model was applied to build a system that includes the stages of analysis, design, implementation, and testing. This research stage was carried out by collecting data through interviews. The data is then input into a decision support system, calculated using the ORESTE method, and stored in a database. This allows decision making with the final results sorted by system from the smallest to the largest value. The results of the study based on the ORESTE method are that Rizka Utami's alternative is the first alternative with a final value of 6.82211. This is because Rizka Utami's alternative meets almost all criteria starting from Performance Assessment, Organizational Needs, Education and Training, Length of Service and Age.